Effectiveness of Think-Pair-Share in a Flipped Classroom for Improving Students’ Cognitive Outcomes on Climate Change - Komang Widiani; Desak Made Citrawathi; Ajeng Purnama Heny; Ni Putu Fani Andriani (SEARCH: Science Education Research Journal, 2026)
Low student engagement and learning readiness remain significant challenges in Biology learning, particularly in the topic of climate change. This study aimed to analyze the effectiveness of the Think-Pair-Share (TPS) learning model integrated with a Flipped Classroom approach in improving senior high school students' cognitive learning outcomes. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of 70 tenth-grade students from SMA Negeri 2 Tejakula, who were assigned to experimental and control groups. Data were collected through cognitive achievement tests and student response questionnaires and analyzed using N-Gain, ANCOVA, and Cohen’s effect size. The results showed that the experimental group achieved a higher mean N-Gain score (0,76) than the control group (0,66). ANCOVA results indicated a significant difference in cognitive learning outcomes between the two groups (p < 0,05). Furthermore, the effectiveness test revealed an effect size of 0,642 which is categorized as medium. In addition, students’ responses to the implementation of the learning model were classified as positive across all indicators. These findings suggest that integrating the Think-Pair-Share (TPS) model with a Flipped Classroom approach effectively enhances students’ cognitive learning outcomes and can serve as an alternative instructional strategy for fostering more active and meaningful Biology learning.